Fair allocations: Making markets work without prices - Christian Basteck (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2023)
Prices can be extremely helpful in creating a good balance between supply and demand. But what if the availability of certain goods should not depend on income or wealth? Christian Basteck explains how allocation in the education sector, for example, can be made fair and efficient without using prices.
Keywords: 300